Transparency in investor-state arbitration: the way forward - Ribeiro, J.; Douglas, Michael (Kluwer Law International, 2015)
The push for transparency in investor-State arbitration is gaining momentum. In July 2013 the United Nations Commission on International Trade Law (UNCITRAL) adopted the UNCITRAL Rules on Transparency in Treaty-based Investor-State Arbitration. (1) In December 2014 the General Assembly adopted the United Nations Convention on Transparency in Treaty-based Investor-State Arbitration (Mauritius Convention on Transparency), (2) providing a streamlined mechanism for States to adopt the Rules on Transparency. These developments are part of a welcomed trend towards transparency in investor-State page "49" arbitration. (3) This article explains why transparency of investor-State arbitration is so important, why the Rules on Transparency should be widely adopted, and how the Mauritius Convention on Transparency can make that happen.